2012
DOI: 10.1111/jvim.12021
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Body Condition Score and Plasma Inflammatory Cytokines, Insulin, and Lipids in a Mixed Population of Light‐Breed Horses

Abstract: Background: Obesity and hyperinsulinemia increase the risk of laminitis in horses and ponies. In mares, obesity also has been associated with increased circulating concentrations of the proinflammatory cytokine, tumor necrosis factor (TNF)-a. The association of other proinflammatory cytokines with body condition score (BCS) and insulin requires further determination.Hypothesis: Plasma concentrations of TNF, interleukin (IL)-1b, IL-6, and serum amyloid A (SAA) will positively correlate with BCS or insulin or bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 47 publications
6
52
2
Order By: Relevance
“…Although adrenal cortical hyperplasia is commonly associated with proliferative pituitary lesions in other species, it is uncommon in horses [10] [17]. Likewise, there was no association between pituitary score and adrenal corticomedullary ratio in the current study.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Although adrenal cortical hyperplasia is commonly associated with proliferative pituitary lesions in other species, it is uncommon in horses [10] [17]. Likewise, there was no association between pituitary score and adrenal corticomedullary ratio in the current study.…”
Section: Discussioncontrasting
confidence: 44%
“…In humans, obesity has also been associated with increased oxidative stress and inflammation [9]. Similarly, in horses, increased levels of the acute phase protein serum amyloid A (SAA), which are indicative of systemic inflammation and oxidative stress, have been associated with both obesity and IR [10]. However, it is unclear if the increased SAA is a cause or effects of the obesity and IR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate a trend of more pro-inflammatory and less regulatory cytokines in females. This is still a controversial issue in horses (Hamza et al, 2008;Uner et al, 2013;Wray et al, 2013), but is in line with higher plasma levels of TNF␣ found in mares than in geldings of mixed breeds and ages (Suagee et al, 2013).…”
Section: Sex Is Relevant For Some Immunological Parametersmentioning
confidence: 82%
“…Moreover, the possible influence of TG and glycerol on plasma leptin release from the adipose tissue is unknown and the role of FFA in the regulation of the leptin level is not clear (Cammisotto et al, 2003). In other studies, the reported connections between plasma leptin and lipid concentrations are more likely to be the effect of the existing energy status of the examined horses (Frank et al, 2006;Pleasant et al, 2013;Suagee et al, 2013).…”
Section: Discussionmentioning
confidence: 95%